Effects of normobaric hypoxic conditions on sleep duration and quality in professional Australian Football League players - Herrera, C.P.; Farooq, A.; Coutts, A.; Bilsborough, J. C.; Hocking, J.; Cordy, J.; Racinais, S.; Buchheit, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Sleeping at simulated hypoxic environments in athletes is a common strategy to enhance performance as part of a `live hightrain low` camp but may be associated with reduced sleep duration and poor sleep quality. The purpose of this study was to investigate, in professional Australian Football League players, the effects of sleeping in a normobaric hypoxic dormitory on sleep using wrist actigraphy. Methods: Actigraphy sleep was measured during a 2-week `live high-train low` camp. After one night at 0m for laboratory adaptation and recovery from travel, sleep data were analyzed from a control group sleeping at normoxia (n=9, 22±2 y, 24.3±1 kg/m2) and compared with a second group sleeping at hypoxia (n=9, 22±2 y, 24.9±1 kg/m2); there was a progressive increase in simulated altitude - two nights at 2500m, two nights at 2800m, and subsequent nights at 3000m. A sleep diary was administered each morning to assess subjective sleep quality. Results: There was a general decline in sleep duration and reduction in sleep quality across the study period in all players. Time in bed, total sleep time, and sleep efficiency were significantly reduced whereas the number of awakenings and total time spent awake after sleep onset were increased (all p<0.05). Comparing groups, time in bed was significantly lower in hypoxia (521.4±13.6) than normoxia (538.6±14.2, p<0.05). Excluding nights (4, 8, and 12) when there was an unrestricted sleep opportunity, total sleep time was significantly lower in hypoxia (430.7±5.0) than normoxia (453.0±5.1, p<0.01). All subjects reported a reduction in subjective sleep quality throughout the training camp but there were no group differences. Discussion: This study provides novel evidence using actigraphy to confirm that sleep duration is reduced under normobaric hypoxic environments between 2500-3000m in Australian Football League players. The reduction in sleep duration was demonstrated only when the sleep period was fixed. In other words, when the sleep period was unrestricted there was no difference in total sleep time. These findings suggest that an extended sleep opportunity may attenuate possible sleep loss in athletes during a `live high-train low` camp.